2011
DOI: 10.1111/j.1570-7458.2011.01198.x
|View full text |Cite
|
Sign up to set email alerts
|

Female‐targeted attractant containing pear ester for Synanthedon myopaeformis

Abstract: When testing pear ester (ethyl‐2,4‐decadienoate) + acetic acid (PEAA) lures to catch codling moths, Cydia pomonella (L.) (Lepidoptera: Tortricidae), in Hungary, significant catches of the apple clearwing moth, Synanthedon myopaeformis (Borkhausen) (Lepidoptera: Sesiidae), were also recorded. This sesiid is one of the most important pests of apple in Europe. Pear ester plus acetic acid lures were attractive to S. myopaeformis no matter whether the two compounds were provided in separate dispensers or mixed toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 27 publications
(35 reference statements)
3
22
0
Order By: Relevance
“…The most recent research done in Hungary (Tóth et al 2012) indicated that lures with pear ester and acetic acid (PEAA) were attractive to S. myopaeformis no matter whether the two compounds were provided in separate dispensers or mixed together in a single dispenser, and a large percentage (40– 80%) of S. myopaeformis caught were females. However, the results of the present study yielded a better-founded sex ratio than those that used PEAA as an additional attractant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent research done in Hungary (Tóth et al 2012) indicated that lures with pear ester and acetic acid (PEAA) were attractive to S. myopaeformis no matter whether the two compounds were provided in separate dispensers or mixed together in a single dispenser, and a large percentage (40– 80%) of S. myopaeformis caught were females. However, the results of the present study yielded a better-founded sex ratio than those that used PEAA as an additional attractant.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to prevent injury to S. myopaeformis can lead to reduced tree vigor and yield, and infested trees are much more vulnerable to infestations of fungal diseases such as canker (Iren et al 1984). Control methods include targeting larvae with insecticides of the pyrethroid group (deltarnetrine (Decis 2,5EC) and alphacypermetrin (Fastac 100EC)) or other chemicals such as motor oil (Erler 2010) and pear ester with acetic acid (Tóth et al 2012). More natural methods based on biological control include bacteria (Shehata et al 1999), nematodes (Kahounova 1991), and fungi (Cossentine 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Considering their responses to PE being synergized by the addition of AA, both Y. scabrella and N. trimaculana appear to be similar to the tortricids C. pomonella (Landolt et al, 2007), C. splendana (Jósvai et al, 2016b), H. nubiferana (Jósvai et al, 2016a) and to the sesiid S. myopaeformis (Tóth et al, 2012). Consequently, the number of families where field activity of PE has been demonstrated increased to three.…”
Section: Discussionmentioning
confidence: 91%
“…The following four treatments were compared in each experiment: PE on its own (6 mg, on rubber or polyethylene bag dispenser); AA on its own (400 mg; in polyethylene bag dispenser); PE (6 mg) and AA (400 mg) loaded into the same polyethylene bag dispenser and unbaited traps. The composition of PE and AA at this ratio was reported to be effective for some pest moths in earlier experiments (Tóth et al, 2012(Tóth et al, , 2014Jósvai and Tóth, 2015). Synthetic PE (98% general purity, minimum 92% isomeric purity) was purchased from Bedoukian (Danbury, CT), while AA (purity 96%) was obtained from Sigma-Aldrich (Budapest, Hungary).…”
Section: Details Of Field Trapping Testsmentioning
confidence: 99%
See 1 more Smart Citation